2012
DOI: 10.1248/bpb.35.317
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Cytochrome P450 2C19 Gene Variations on Pharmacokinetic Parameters of Thalidomide in Japanese Patients

Abstract: Purpose: Cytochrome P450 (CYP)2C19 polymorphisms may partly explain the variability of thalidomide concentration and adverse drug effects by altering its metabolism. To compare the genetic and clinical factors responsible for the adverse effects and efficacy of thalidomide treatment, we investigated CYP2C19 genetic polymorphisms in Japanese subjects. Materials and Methods: Variations in the CYP2C19 gene in 6 patients treated with thalidomide were analyzed. The dosage of thalidomide, concentrations of (R)-and (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 18 publications
0
10
0
Order By: Relevance
“…Previous studies have shown that CYP2C19 plays a vital role in the metabolization of thalidomide . A Japanese study found that patients with CYP2C19 PM tended to have high serum thalidomide concentrations, and they were at high risks of polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin change syndrome and amyloid light chain amyloidosis .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have shown that CYP2C19 plays a vital role in the metabolization of thalidomide . A Japanese study found that patients with CYP2C19 PM tended to have high serum thalidomide concentrations, and they were at high risks of polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy and skin change syndrome and amyloid light chain amyloidosis .…”
Section: Discussionmentioning
confidence: 99%
“…Thalidomide is transformed into 5‐hydroxythalidomide (5‐OH) and cis ‐5′‐hydroxy thalidomide by cytochrome P450 2C19 (CYP2C19) isozyme‐mediated oxidation in human and animal liver microsomes . Both recombinant CYP2C19 and anti‐CYP2C antibodies have been reported to contribute to the metabolism of thalidomide, indicating a potential role of CYP2C family in this process . Moreover, Li et al have suggested that CYP2C19 genotypes are related to the efficacy of thalidomide in multiple myeloma in clinical setting, although their results are inconsistent with those of Vangsted et al's study .…”
Section: Introductionmentioning
confidence: 89%
“…Two variants resulting in the synthesis of non-functional truncated proteins, Ile215_Pro227del fs*20 or CYP2C19*2 (c.681G>A, which results in an aberrant splicing of exon 5) and Trp212X or CYP2C19*3 (c.636G>A), have been associated with a lack of response to thalidomide in patients with multiple myeloma 78,79 . The CYP2C19*2 variant has also been associated with lower drug efficacy in cyclophosphamide-treated patients as a result of inefficient activation of the prodrug 80 .…”
Section: Moc-2mentioning
confidence: 99%
“…[25][26][27][28] There was some influence of genetic polymorphism in CYP2C19 on the blood concentration of thalidomide in MM, amyloid light chain amyloidosis, and polyneuropathy, organomegaly, endocrinopathy, monoclonal gammopathy, and skin changes (POEMS) syndrome related to MM in Japanese patients. 29) It has been reported that decreased formation of thalidomide metabolites would be expected with defective alleles of CYP2C19 compared to wild-type in clinical treatment with thalidomide plus dexamethasone. 30) Association studies of genetic variation and treatment effect may serve as predictive markers for the effects of treatment and can also uncover biological pathways behind drug effects.…”
Section: Cyps and Transportersmentioning
confidence: 99%
“…Only one patient with the CYP2C19*2/*2 genotype taking thalidomide developed dyspnea as a side effect, but it improved following the termination of thalidomide. 29) Peripheral neuropathy is a common side effect of thalidomide and often calls for the cessation of therapy when the symptoms are severe. 12) The thalidomide-related peripheral neuropathy associated with ABCA1 (rs363717), ICAM1 (rs1799969), PPARD (rs2076169), SERPINB2 (rs6103), and SLC12A6 (rs7164902) SNPs and an individual's risk of developing peripheral neuropathy after thalidomide treatment can be mediated by polymorphisms in genes governing repair mechanisms and inflammation in the peripheral nervous system.…”
Section: Cyps and Transportersmentioning
confidence: 99%